Impact of Fermented Dragon Fruit Peel (Hylocereus Sp.) Juice in Drinking Water on the Performance and Quality of Japanese Quail Eggs - Dewi, Gusti A.M.K.; Umiarti, Apni T.; Wirapartha, Made (KnE Life Sciences, 2022)
The purpose of this 10-week study was to examine the impact of fermented dragon fruit peel (Hylocereussp) juice in drinking water on the performance and quality of Japanese quail eggs. A total of 200 two-week-old quails were included using a completely randomized design that included five treatments and four replications, each with ten quails. R0 = drinking water without dragon fruit peel juice; R1 =drinking water containing 1% dragon fruit peel juice; R2 =drinking water containing 1% fermented dragon fruit peel juice; R3 =drinking water containing 3% dragon fruit peel juice; R4 =drinking water containing 3% fermented dragon fruit peel juice. The performance and quality of the Japanese quail eggs were measured.The study’s findings revealed that treatments R2, R3, and R4 significantly improved quail performance, body weight gain, final body weight, FCR, and egg quality, weight, HU, and yolk color when compared to R0. Keywords: dragon fruit peel juice, performance, eggs quality, Japanese quail